2012
DOI: 10.1017/s1049023x12000933
|View full text |Cite
|
Sign up to set email alerts
|

In the Line of Duty: A Study of Ambulance Drivers During the 2010 Conflict in Kashmir

Abstract: The atmosphere of conflict on the streets of Kashmir impacted the ambulance drivers adversely, both physically as well as mentally. The stress faced by these professionals in conflict zones during their duty hours should be recognized, and corrective measures must be put in place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Taylor found that assaults were the most common near‐miss events for EMS personnel . Bernaldo‐De‐Quirós and Dhar described the psychological impact of violence among EMS personnel …”
Section: Resultsmentioning
confidence: 99%
“…Taylor found that assaults were the most common near‐miss events for EMS personnel . Bernaldo‐De‐Quirós and Dhar described the psychological impact of violence among EMS personnel …”
Section: Resultsmentioning
confidence: 99%
“…The main reasons for the high prevalence of workplace violence in the pre‐hospital setting include critical workplace conditions, working in unpredictable environments (Bigham et al, ; Gormley et al, ), unexpected deaths, driving accidents and severe injuries (King, ; Lindström, Bohm, & Kurland, ). In this regard, studies have reported the annual rate of all types of workplace violence experienced by EMTs as follows: 65% in Saudi Arabia (Alharthy et al, ); 75% in Iran (Rahmani et al, ); 67% in Turkey (Deniz, Saygun, Eroğlu, Ülger, & Azapoğlu, ); 66% in Sweden (Petzäll et al, ); 83% in India (Dhar et al, ); 88% in Australia (Boyle, Koritsas, Coles, & Stanley, ); and 75% in Canada (Bigham et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…While any politically charged conflict area poses challenges to healthcare workers (Dhar ), the challenges for nurses in the West Bank are different from those in other Middle Eastern countries (Mahmoud ). In 2002, Israel constructed a wall that separated Israel and the West Bank.…”
Section: Introductionmentioning
confidence: 99%